Comparative analysis of cross-wind load code for high structures with circular sections. (September 2022) - Wang, Lei; Wang, Zheng; Huang, Nan; Fan, Xing-Yan; Zhang, Zhen-hua
Abstract: Many high-flexible structures with circular sections (chimneys, etc.) tend to be damaged by vortex-induced vibration (VIV in short). As the direct guidance of wind-resistant design of circular high structures, the wind load code is responsible for wind-induced damage. In view of so many failure cases of circular high structures, it is necessary to study the applicability of current wind load codes. In this paper, the VIV displacements of six chimneys are calculated using European (approach 1, 2), Chinese, Japanese, Canadian, and American wind load codes/recommendations, respectively, and the calculated displacements are compared with the full-scale measured results. The comparison shows that for steel chimneys, the displacements calculated by Japanese recommendation and Chinese code are about only 30% of the full-scale measured value, and those calculated by Canadian code and approach 1 of European code are about 70% of the measured value. For reinforced concrete (RC) chimneys, the calculated displacements of Chinese codes are smaller than the full-scale measured values, while the calculated values of other codes are far greater than the full-scale measured results, with the difference between them even more than ten times. On the whole, there is a significant difference between the results of the VIV displacement calculated by the wind load codes/recommendations and the actual measured value, and the calculated results of current codes/recommendations are differ from one another, thus giving rise to a contradictory phenomenon of "the same structure, but different design wind load" and making the wind-resistant design of circular high structure kind of blind. The purpose of this discussion is to clarify the objective problems of current wind load codes of circular tall structures, which can provide a reference for further research.